World society and the transformation of national defense: exploring world cultural impact on security and military - Anja P. Jakobi (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2009)
In this paper, I explore the applicability of sociological institutionalism for the analysis of security and the military. Based on cross-sectional data from 50 countries, I show how values linked to the nation state and security are related to world cultural ideas and the diffusion of rationalized organizational models. Such linkage could explain the transformation of the military as a common and worldwide trend, being based on political and societal preconditions that converge across countries. The paper is structured as follows: I first introduce basics on military transformation in the course of time, before I turn to the framework of sociological new institutionalism. I particularly emphasize world cultural values and rationalized organizational forms as well as the diffusion process linked to them. In the empirical analysis, I first show how values linked to individualism, the nation state and world society are linked to national security. As suggested by sociological institutionalism, individual values and the importance of world society are wide-spread and also linked to less nationalism and a lower significance for security and defense. However, the nation state is still an important point of reference. In the second empirical analysis, I turn to the organizational form of the military, showing changing aims, and changed ways of organizing the service. Here we find that the military has indeed transformed to an organization with features comparable to the non-military world, supporting sociological institutionalist claims. In sum, the findings point towards changed security policies induced by world cultural norms. However, further analyses are needed to explore this relationship in more detail and to ultimately test this theory against functionalist explanations. – – Dieses Arbeitspapier analysiert Sicherheitspolitik und Militärreformen aus der Perspektive des soziologischen Institutionalismus. Basierend auf Daten aus 50 Staaten wird gezeigt, dass Werte und Organisationsformen in diesem Feld zunehmend Trends einer 'Weltkultur' entsprechen. Dazu führt das Papier zunächst kurz in aktuelle Reformen des Militärs ein, bevor in einem theoretischen Teil zwei Diskussionen des soziologischen Institutionalismus ausgeführt werden, genauer die Verbreitung kultureller Werte basierend auf Individualismus und einem geteilten Welthorizont, sowie die Einführung rationalisierter Organisationsformen in verschiedensten gesellschaftlichen Bereichen. In der empirischen Analyse wird dann gezeigt, dass sich die angenommene Weltkultur in der Tat in sicherheitsrelevanten Werten und Auffassungen niederschlägt und dass das Militär sich zunehmend 'rationalisiert' und 'individualisiert' organisiert. Die Ergebnisse unterstützen theoretische Annahmen des soziologischen Institutionalismus, sollten aber in weiteren Untersuchungen noch verstärkt gegen rivalisierende funktionalistische Theorien getestet werden.
Keywords: 350